Raman endoscopy for monitoring the anticancer drug treatment of colorectal tumors in live mice. Issue 19 (24th August 2017) - Taketani, Akinori; Andriana, Bibin B.; Matsuyoshi, Hiroko; Sato, Hidetoshi
Abstract : A miniaturized Raman endoscope (mRE) system was employed to study the effects of anticancer treatment on colorectal tumors in a live murine model. Abstract : A miniaturized Raman endoscope (mRE) system was employed to study the effects of anticancer treatment on colorectal tumors in a live murine model. The endoscope is narrow enough to observe the inside of the mouse colon under anesthesia. It has a channel for a ball lens mounted on a hollow fiber Raman probe (BHRP) to measure any targeted point under the visual control of the endoscope. Colorectal cancer tissue was observed to study the alterations of the tissue in response to anticancer drug treatment. Three anticancer drugs, 5-fluorouracil (5-FU), cisplatin (CDDP), and docetaxel, were employed. Although no alteration was recognized in the endoscopic visual observations at 2 weeks after the drug treatment, the Raman spectra obtained in the live mouse colon indicated that molecular changes of lipids and proteins were observed. This study demonstrates that in situ Raman analysis is highly sensitive for detecting the effects of anticancer drugs.